Advances in electrochemical simulation and its application to electroanalysis - Barnes, EO (2014)
This thesis is concerned with the simulation of various electrochemical experiments and its application to electroanalysis. Chapter 1 outlines the fundamental principles of electrochemistry which are of importance for the reading of this thesis. Chapter 2 then outlines the methods used in the numerical simulation of electrochemical experiments. Chapters 3 and 4 are concerned with the electrochemistry of nanoparticles, and how this is affected by the presence of near wall hindered diffusion. In Chapter 3, a computational model to simulate anodic particle coulometry of nanoparticles in the presence of hindered diffusion is developed, and the effect of this hindered diffusion investigated. The model is then applied to simulate experimental data. Chapter 4 looks at the effect of hindered diffusion on the adsorption of nanoparticles on electrode surfaces, and investigates the effects of this adsorption on electrochemical experiments with nanoparticles generally. Chapters 5, 6 and 7 are concerned with band electrodes in isolation, in a pair and in an array respectively. In Chapter 5, a model to simulate double potential step chronoamperometry at an individual band electrode is developed, and used to successfully simulate experimental data. Chapter 6 looks at dual band electrodes used in generator-collector mode, and how this can be used to simultaneously measure the concentration of two species in solution. Chapter 7 looks at interdigitated arrays of band and ring electrodes in generator-collector mode, and develops a model to simulate cyclic voltammetry in both cases, as well as investigating under what conditions interdigitated ring arrays may be modelled as interdigitated band arrays. Chapter 8 develops a model to simulate chronoamperometry and cyclic voltammetry at porous electrodes, and investigates the consequences for electroanalysis of having a porous layer. Finally, Chapter 9 investigates the Marcus-Hush theory of electron transfer kinetics, and looks at the effect of the kinetically limited currents resulting from this theory to the equivalence relation between microdisc electrodes and sphere-on-a-surface electrodes.